Structural performance on beam with diferent size and spacing of link - Nur Fadzilah Md Isa (School of Environmental Engineering, University Malaysia Perlis, 2013)
This report conducted the experimental studies to know the performance on beam with different size and spacing of link. The objective of this research is to design beam and reinforcement required for beam using British Standard, to determine the flexural strength of the beam with different arrangement and size of reinforcement and to identify crack pattern between different arrangement and size of reinforcement on beam.